PENGARUH KECEPATAN PROMOSI KARIR DAN ORIENTASI KAPABILITAS SUPERVISOR TERHADAP KEINGINAN BERPINDAH PADA AGEN ASURANSI PT PRUDENTIAL LIFE ASSURANCE CABANG SAMARINDA - Smith, Alan; Kaluge, David; Umiriyana, Umiriyana (Jurnal Akun Nabelo: Jurnal Akuntansi Netral, Akuntabel, Objektif, 2020)
The purpose of this study was to examine the effect of the speed of career promotion and the orientation of the supervisor's capability against the desire to move. The method used is purposive sampling with non-probability sampling technique. The sample in this study are 40 respondents with criteria work at least 1 year and work as insurance agent. The hypothesis test used is Multiple Linear Regression using SPSS version 23. The results of this study indicate that: The speed of career promotion has a significant effect on switching desire, the orientation of the capability of the supervisor has a significant effect on switching desire, and the speed of career promotion and the orientation of the supervisory capability have a negative and significant effect on the desire to move.